QUO VADIS SOCIETY? An X-ray of the social space in which we are living - Cambronero Torres, Andrei (2018)
The article evidences some of the particularities society possesses in actuality. That classical concept of the social theory appears today, just like everything that seemed strong, blurred: the uncertainty has also touched the object of Socioglogy. This text finds itself structured in four sections; the first is a sketch of what are some characteristics of the current social order to present the challenges, that from the Social Sciences, this new structure has. Then, three relatively new concepts are presented, which facilitate the understanding of contemporary dynamics and finally, there’s a brief description of the attributes of the society.